Meaning of the reform for interregional Law - Arenas García, Rafael (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The historical origin of the plurality of Spanish civil laws allows us to understand the particularities of the interregional law system and its current characteristics. This contribution examines the evolution of this normative plurality, as well as the integration of the different Spanish laws from the Modern Age to codification. From this point, it examines how the maintenance of the plurality of Spanish civil laws and the regulation of interregional law are interrelated, with special attention to the principles introduced in the Civil Code of 1889 and maintained in the 1974 revision. Regarding the latter, the technical improvements introduced and the way specific interregional law problems that required a differentiated solution from that given to international law conflicts were addressed are highlighted.
Keywords: PIL; Interregional Law; History of PIL; Internal conflicts